Wuling capsule alleviates hyperuricaemia and protects UA- injured HK-2 cells by regulating uric acid transporter proteins - Li, Nan; Liu, Hongna; Song, Zhongxing; Zhou, Rui; Tang, Zhishu; Xu, Hongbo; Shi, Xinbo; Liu, Yanru; Ni, Jian (Frontiers in Pharmacology, 2025)
IntroductionWuling capsule is a Chinese patent medicine mainly used for the treatment of chronic liver disease in clinical practice. Our previous work has revealed that Wuling capsule could inhibit liver fibrosis by regulating macrophage polarization, and firstly demonstrated its anti-gout effects on monosodium urate (MSU)- induced acute gouty arthritis (AGA) in rats. High uric acid (UA) levels are known to be the primary cause of gout. Therefore, this study investigated the UA lowering, kidney protection effects and underlying mechanisms of Wuling capsule in vivo and in vitro, and also determined its key bioactive constituents.MethodsThe efficacy of Wuling capsule for HUA symptoms in rats was evaluated. Histopathological analysis of liver and kidney tissues were detected by HE staining. The biochemical indices were measured using specific kits. The main constituents of Wuling capsule and its medicated serum were analyzed by UPLC-QTOF-MS/MS. Protective effects of saikosaponin A, tanshinone IIA, schisandrol B, and ganoderic acid A on UA-injured HK-2 cells were assessed via Hoechst 33342/PI staining and flow cytometry. Molecular docking and dynamics simulation predicted the binding energy and stability of these constituents to UA related transporters. The mRNA and protein expression levels of UA related transporters were examined using RT-qPCR and Western blotting.ResultsIn HUA rats, Wuling capsule significantly reduced the serum UA level and xanthine oxidase (XOD) content in both serum and liver. Furthermore, it improved liver function markers (ALT, AST) and renal injury indicators (Cr, BUN), ameliorated renal tubule dilation and inflammatory infiltration in the kidney, and regulated the mRNA and protein expression of UA related transporters (URAT1, GLUT9, ABCG2 and OAT1). In vitro, the main constituents of Wuling capsule (saikosaponin A, tanshinone IIA, schisandrol B and ganoderic acid A) improved cell viability and inhibited cell apoptosis in UA-injured HK-2 cells. Subsequently, its four serum constituents also significantly regulated the mRNA and protein expression of URAT1, GLUT9, and ABCG2 selectively.DiscussionThis work demonstrated the therapeutic effect of Wuling capsule on HUA by protecting liver and kidney function and regulating UA related transporters. These findings provide novel support for the further clinical application of Wuling capsule.